Effect of α-Tocopherol on Viability, Lipid Peroxidation and Oxidative Stress of Cryopreserved Ovine Preantral Follicle - Kaushik, Kalpana; Pulukuri, Johnson; Tej, NikhilK; Krishna, Kavya; Gupta, Paluru S.P.; Nandi, Sumanta; Mondal, Sukanta (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Vitrification of preantral follicles is a promising technique to preserve female fertility. The aim of the present study was to evaluate the effect of supplementation of α-tocopherol in the vitrification solution on the viability, lipid peroxidation and mRNA expression of superoxide dismutases (SOD1 and SOD2) in vitrified cultured ovine preantral follicles at day-6 and day-12. Preantral follicles (200-300 µm) were isolated from the ovine ovaries by the mechanical method and were distributed separately to the vitrification medium supplemented with 10 mM and 20 mM of α-tocopherol. After a week, the follicles were thawed and analyzed for follicular viability by trypan blue dye exclusion method and subjected to in vitro culture (IVC) for 6 and 12 days. Our results revealed that the significant increase (p<0.05) of viability in 20 mM α-tocopherolsupplemented vitrified group when compared to the vitrified without α-tocopherol group. On day-6 of IVC, malondialdehyde (MDA) concentration was significantly(p<0.05) higher in vitrified group without α-tocopherol in comparison to vitrified supplemented with 20 mM of α-tocopherol and control fresh groups. However, no significant difference in MDA content was found among the groups at day-12. The mRNA expression level of SOD1 at day-6 was significantly (p<0.05) higher in vitrified with 20 mM of α-tocopherol and control fresh groups compared to the vitrified without α-tocopherol and with10 mM α-tocopherol groups. The expression pattern of SOD2 was significantly (p<0.05) higher in control fresh group compared to the other groups at day-6 and day-12 of IVC.We conclude that lowering the vitrification-induced lipid peroxidation of preantral follicles by α-tocopherol at 20 mM concentration may be mediated by increasing SOD expression during IVC.